(Nie) tylko: za ile? Motywacja jako element nowoczesnego zarządzania szkołą - Szafran, Joanna (Wydawnictwo Naukowe UAM, 2014)
Management researchers and practitioners believe that involvement of the members of an organization is essential for it to achieve its goals. Dynamic changes in needs structures and in both favorable and unfavorable factors that help to fulfill those needs, are basic elements for employees’ activity. It is highly probable that effectiveness in management involves finding solutions and creating a system in which one will receive actually expected gratifications, offering in return full professional involvement. It is motivation and the role of the manager (school’s headmaster) in this process that is essential to the contents presented here. The article describes certain motivation concepts, which may serve as an inspiration for practical implementing of scientific achievements in order to improve team management, quality and effectiveness of the whole school activity. Considerations are accompanied by an assumption that properly used knowledge combined with adequate managerial competence, including the specifics of a teaching profession environment, is an important impact tool.
(Not) Only: How Much? Motivation as a Part of a Modern School Management
Keywords: management; motivation; manager/school’s headmaster; effective leadership